Mouse Cursor Control System Based on Hand Gesture. (2016) - Grif, Horatiu-Stefan; Farcas, Cornel Cristian
Abstract: The apparition on market of the low-cost webcams with, at least, satisfactory qualities open up new directions regarding the implementation of human computer interaction (HCI) interfaces. The paper presents a HCI interface for mouse cursor control. The purpose of the implemented solution is to control the mouse cursor by user hand gestures captured through a webcam. For improving the gesture recognition based on the fluctuation of illuminance levels the finger strips color detection was used. The results reveal the good behavior of the system in low light condition.